Pengaruh Karakteristik Pekerjaan, Karakteristik Organisasi dan Karakteristik Individu Terhadap Kepuasan Kerja Pegawai (Studi Kasus Pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Malang) - Fadlullah, M Agus; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to determine and analyze the influence of job characteristics, organizational characteristics and employee job satisfaction variables in the Malang City Population and Civil Registration Service case study. The sample used was 80 employees of the Malang City Population and Civil Registration Service. The data collection methods used in this research were questionnaires and Google Form.Based on the research results, it is known that job characteristics, organizational characteristics and individual characteristics simultaneously influence the job satisfaction variable of Malang City Population and Civil Registration Service employees. Job characteristics have a significant influence on job satisfaction. Malang City Population and Civil Registration Service employee variables, organizational characteristics have a significant effect on the job satisfaction variable of Malang City Population and Civil Registration Service employees, individual characteristics have a significant effect on the job satisfaction variable of Malang City Population and Civil Registration Service employees, individual characteristics have a significant effect on variables job satisfaction of employees of the Malang City Population and Civil Registration Service, individual characteristics have a significant effect on the variable Job satisfaction of employees of the Population and Civil Registration Service of Malang City, individual characteristics have a significant effect on the variable Job satisfaction of employees of the Population and Civil Registration Service of Malang City. Keywords : Job Characteristics, Organizational Characteristics, Individual Characteristics And Employee Job Satisfaction